2023
DOI: 10.3897/zookeys.1151.100766
|View full text |Cite
|
Sign up to set email alerts
|

New records of water mites (Acari, Hydrachnidia) from Portugal revealed by DNA barcoding, with the description of Atractides marizae sp. nov.

Abstract: This study presents the first results of DNA barcoding of water mites from Portugal. DNA barcodes were recovered from 19 water mite specimens morphologically assigned to eight species, seven of them newly reported from Portugal. Two species, Torrenticola hispanica (Lundblad, 1941) and A. cultellatus (K. Viets, 1930) were discovered more than 80 years after they were first described, and Atractides marizaesp. nov. is described as new for science.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…For example, our COI phylogenetic tree revealed that the A. nodipalpis lineage (BIN ACA0209), which also includes individuals collected near the locus typicus, appeared as sister to the clade comprising A. ruffoi Gerecke & Di Sabatino, 2013 (Corsica;Gerecke & Di Sabatino 2013) and A. marizae Pešić, 2023 (Portugal;Pešić et al 2023). All three species are primarily defined by a similar shape of the male genital plate with a peg-or drop-shaped anteromedial fissure.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, our COI phylogenetic tree revealed that the A. nodipalpis lineage (BIN ACA0209), which also includes individuals collected near the locus typicus, appeared as sister to the clade comprising A. ruffoi Gerecke & Di Sabatino, 2013 (Corsica;Gerecke & Di Sabatino 2013) and A. marizae Pešić, 2023 (Portugal;Pešić et al 2023). All three species are primarily defined by a similar shape of the male genital plate with a peg-or drop-shaped anteromedial fissure.…”
Section: Discussionmentioning
confidence: 97%
“…None of the DNA sequences showed evidence of pseudogenes. The final dataset includes 180 COI sequences of the genus Atractides downloaded from the respective sequence data archives; 175 sequences were taken from Pešić et al 2023 (the complete list available at https:// doi.org/10.3897/zookeys.1151.100766.suppl1) and five private sequences representing A. spinipes (HYDAS082-22, HYDAS162-22) from Austria, A. pumilus (NOVMB065-21) from France, and A. glandulosus (HYDOC007-22) from Serbia were taken directly from the BOLD. MEGA X software (Kumar et al 2018) was used to calculate Neighbour-Joining (NJ) trees based on K2P distances (standard for barcoding studies) and pairwise deletion of missing data.…”
Section: Molecular and Dna Barcode Analysesmentioning
confidence: 99%